Short Communication: The normal karyotyping result of Indonesian native breed bull qualified for artificial insemination - GATOT CIPTADI; MUH NUR IHSAN; VERONICA M. ANI NURGIARTININGSIH; IRSANTI PUTRI ARDYAH; MUDAWAMAH MUDAWAMAH (Biodiversitas Journal of Biological Diversity, 2017)
Ciptadi G, Ihsan MN, Nurgiartiningsih VMA, Ardyah IP, Mudawamah M. 2017. Short Communication: The normal karyotyping result of Indonesian native breed bull qualified for artificial insemination. Biodiversitas 18: 1462-1467. Bali and Madura cattle are important native breed in Indonesia, both descendants of wild banteng (Bos javanicus). These breeds are categorized as a small type beef cattle, and are indigenous, well adapted and, have high resistance to diseases. The aims of this research were to analyze dendrograms of these breed and karyotype breeding bull selected for Artificial Insemination (AI). The result showed that the 2n diploid number of chromosome of all cattle was 60 and they were considered normal, based on the number and structure of chromosomes. Fiftyeight acrocentric autosomes and 2 sex chromosome were observed, including a submetacentric X-large chromosome submetacentric and a small Y chromosome. Dendrogram analysis showed that Bali and Madura cattle were closely related and derived more from their ancestor wild banteng than from Java cattle. It is recommended to perform a chromosomal investigation of breeding bulls especially those used for freezing semen production and AI implementation.